A class of diffusion problem of Kirchhoff type with viscoelastic term involving the fractional Laplacian - LAPA, Eugenio Cabanillas; HUARINGA SEGURA, Zacarias L.; BERNUI BARROS, Juan B.; TRUJILLO FLORES, Eduardo V. (Studia Universitatis Babeș-Bolyai Mathematica, 2020)
This work is concerned with a class of diffusion problem of Kirchhoff type with viscoelastic term and nonlinear interior source in the setting of the fractional Laplacian. Under suitable conditions we prove the existence of global solutions and the exponential decay of the energy. Mathematics Subject Classification (2010): 35K55, 35R11, 35B44, 35Q91.